LOLA: enrichment analysis for genomic region sets and regulatory elements in R and Bioconductor. (27th October 2015) - Sheffield, Nathan C.; Bock, Christoph
Abstract : Summary: Genomic datasets are often interpreted in the context of large-scale reference databases. One approach is to identify significantly overlapping gene sets, which works well for gene-centric data. However, many types of high-throughput data are based on genomic regions. Locus Overlap Analysis (LOLA) provides easy and automatable enrichment analysis for genomic region sets, thus facilitating the interpretation of functional genomics and epigenomics data. Availability and Implementation: R package available in Bioconductor and on the following website: http://lola.computational-epigenetics.org . Contact : nsheffield@cemm.oeaw.ac.at or cbock@cemm.oeaw.ac.at